Penentuan Premi Tahunan Dan Cadangan Manfaat Asuransi Jiwa Dwiguna Murni pada Status Last Survivor dengan Tiga Orang Tertanggung - Fika Riza Syifamillah; Emy Siswanah; Seftina Diyah Miasary (UJMC (Unisda Journal of Mathematics and Computer Science), 2022)
Last-survivor life insurance is life insurance with more than one life (multiple life) in which premium payments end when the policyholder dies for the last time. Last-survivor status can be applied to various types of insurance, including pure endowment life insurance. Pure endowment life insurance is insurance that provides a death benefit if the insured is still alive within the agreed timeframe. Furthermore, two costs that insurance companies must consider are the amount of premiums and benefit reserves. The premium is the amount of money paid by the insurer to the insurer for their participation in the insurance, while the benefit reserve is the amount of funds that the insurance company needs to prepare to pay losses to the participant during the coverage period. The purpose of this study is to calculate the annual premiums and reserves for pure endowment life insurance benefits based on last survivor status for three insured people. Based on the results of calculating the benefit reserve using the prospective method, the older the insurance member, the lower (smaller) the chance of survival. That is, the greater the likelihood that the three members will die before the insurance contract expires, the less likely the insurance company will pay the sum insured. This causes the premium to be paid to be smaller. The value of the benefit reserve from the initial year of insurance to the end of the insurance contract period, which is the 25th year, is getting smaller every year.